A versatile ionic strength sensitive tag from a human GM CSF derived linear epitope - Perotti, Norma Maria (2013)
A 7-mer hGM-CSF-derived linear epitope (APARSPS) is herein described as a novel and small tag taking into account its particular binding affinity in native conditions that could be easily modified by increasing or lowering the ionic strength. Thus, a 3.4 or 3.8-fold binding increment was observed in high NaCl concentration when the tag was fused to IFN-α2b or when the peptide was in its native environment, respectively. The high salt concentration increased the affinity of the binding interaction and improved the APARSPS epitope binding to the paratope allowing one to design an immunoaffinity chromatography purification step in which the high ionic strength was useful to adsorb the fusion protein to the immunoaffinity matrix and the low ionic strength at pH 9 was valuable to desorb it (a 470-fold purification with a 94%-purity was attained in only one step). Also, this short tag did not affect the functionality of the fusion protein and it was able to be detected both in the natural molecule (hGM-CSF) as in the tagged one with the same high detection limit: 273 pg of each protein.